A study on volatile metabolites screening by HS‐SPME‐GC‐MS and HS‐GC‐IMS for discrimination and characterization of white and yellowed rice. Issue 2 (18th February 2020) - Zhang, Xiaoxu; Dai, Zhen; Fan, Xiaojing; Liu, Meng; Ma, Jianfei; Shang, Wenting; Liu, Jinguang; Strappe, Padraig; Blanchard, Chris; Zhou, Zhongkai
Abstract: Background and objectives: Yellowed rice results in serious economic losses to grain industry. This study attempted to profile the volatile metabolites in before‐ and after‐yellowing rice of five Chinese common rice cultivars. Application untargeted metabolomics approach to discover the biomarkers in yellowed rice. Findings: The volatile metabolites were detected by headspace‐gas chromatography–ion mobility spectrometry (HS‐GC‐IMS) and headspace solid‐phase microextraction–gas chromatography‐mass spectrometry (HS‐SPME‐GC‐MS). Yellowed rice emitted more aldehydes, alcohols, furan, and less ester than white rice. Partial least squares‐discriminant analysis (PLS‐DA) based on GC‐MS and GC‐IMS data was revealed a good classifying tool for white and yellowed rice. Hexanal, nonanal, octanal, 1‐pentanol, and 2‐pentyl‐furan were selected as the potential markers by the variable importance in projection (VIP) variable selection method. All of these markers were associated with fatty acid oxygenation. Conclusions: Comparative analysis and biomarker identification of the volatile metabolites of different cultivars of Chinese yellowed rice lay a foundation for research on yellowing mechanism. Significance and novelty: The results of the current study provide a useful basis in the rice yellowing mechanism study. Additionally, a rapid rice aroma analysis method using GC‐IMS was developed. So in the future, yellowed rapid reorganization GC‐IMS technology could be a preferred choice.